Random or selective neuroanatomical connectivity. Study of the distribution of fibers over two populations of identified interneurons in cerebral cortex - Vinkenoog, Marjolein; van den Oever, Michel C.; Uylings, Harry B.M.; Wouterlood, Floris G. (Brain research. Brain research protocols, 2005)
We present a neuroanatomical tracing method in a stereological approach to study the proportional distribution of fibers of a particular projection over two chemically different populations of neurons. The fiber projection from the presubiculum to the medial division of the entorhinal cortex of the rat serves as a model projection. Potential target interneurons express calcium binding proteins, either parvalbumin or calretinin. The three markers were simultaneously stained in one and the same histological section. The procedure is according to a three-phase procedure, i.e., in vivo tracer injection phase, histology phase, laserscanning phase. Steps involved are: (1) Surgical application to the presubiculum (injection) of the neuroanatomical tracer, biotinylated dextran amine (BDA), with the purpose of labeling fibers innervating the entorhinal cortex. After surgery, transport of the tracer takes place during the one-week survival period; (2) Fluorescence detection of the labeled fibers through staining with fluorochromated avidin (avidin-Alexa Fluor 488™ [green fluorescence]); (3) Simultaneous Immunofluorescence detection of two interneuron markers (using the appropriate primary antibodies and secondary antibodies conjugated to the fluorochromes Alexa Fluor 594™ [red fluorescence] and Alexa Fluor 633™ [infrared fluorescence]); (4) Acquisition of low-magnification images in a confocal laserscanning microscope and the preparation on a computer of a montage image covering the entire entorhinal cortex; (5) Overlaying this montage with a sampling grid; (6) Acquisition at high magnification of Z-series of confocal images in a statistical valid way based on this grid. Each marker was visualized in its own laser excitation/emission channel: 488, 568 and 647 nm; (7) Image processing and 3D reconstruction followed by evaluation of the results. The present approach can be used to examine whether or not a particular class of chemically identified neurons receives preferential innervation by a particular fiber projection.